Attitude toward fashion influencers and its impact on purchase behavior: the roles of brand attitude and purchase intention - Handranata, Yunita Wijaya; Kalila, Shifa (Frontiers in Communication, 2025)
IntroductionThe rise of social media has transformed fashion influencers into key players in shaping consumer attitudes and behavior, especially among Generation Z. However, the psychological mechanisms that underlie the relationship between influencer perception and consumer purchase behavior remain underexplored, particularly in emerging markets like Indonesia. This study investigates how attitudes toward fashion influencers affect purchase behavior, mediated by brand attitude and purchase intention.MethodsGrounded in the Theory of Planned Behavior (TPB), this study examines the influence of perceived credibility, influencer expertise, and perceived behavioral control on consumers' attitudes toward fashion influencers. Data were collected through an online questionnaire distributed to 290 Indonesian women, with 251 valid responses analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0.ResultsAll hypothesized relationships were supported. Perceived credibility had the strongest effect on attitude toward influencers, followed by perceived behavioral control and influencer expertise. Attitude toward influencers significantly influenced brand attitude and purchase intention. Brand attitude also served as a strong mediator between influencer attitude and purchase intention. Finally, purchase intention had a strong and direct impact on actual purchase behavior.DiscussionThe findings highlight the pivotal role of influencer credibility and brand attitude in shaping purchase outcomes. The near-complete transfer of positive sentiment from influencer to brand emphasizes the influencer's dual function as both a communicator and co-creator of brand value. These insights extend TPB and offer actionable guidance for marketers targeting Gen Z consumers through digital platforms.